Mathematical Models of Growth and Feed Intake in Rambon Ducks - Anang , Asep; Setiawan, Iwan; Indrijani, Heni; Lan, Limai (International Journal of Poultry Science, 2017)
Objective: This study evaluated the growth and feed intake of Rambon ducks, a type of local Indonesian ducks. Materials and Methods: This study evaluated growth using 6 models, including the Brody, Gompertz, Logistic, Morgan Mencer Flodine (MMF), Richards and von Bertalanffy models. The feed intake model was estimated using the rational function equation. A total of 80 selectively-bred layer ducks (40 males and 40 females) were reared for 22 weeks. Results: All growth models applied were a good fit for both female and male ducks. The Logistic model with three parameters had the best fit with the highest correlation beween actual and predicted values and lowest standard error of estimation. High correlations also indicated that the rational function model had a good fit and successfully predicted feed intake of the ducks from hatching to 22 weeks. Conclusion: The Brody, Gompertz, Logistic, Morgan Mencer Flodine, Richards and von Bertalanffy models had a good fit and successfully predicted the growth of Rambon ducks from hatching to 22 weeks, however, the Logistic model had the best fit. The rational function model also had a good fit and successfully predicted feed intake of the ducks from hatching to 22 weeks.